Simplicity : the secret to effective marketing - Goh, Sunny T. H. (Malaysia, 2004)
This book help you develop simple-mindedness. Your simple-mindedness will enhance your role and help you in supporting or contributing effectively to marketing strategy formulation and execution.Complex-minded marketers are confused marketers. They're insecure and incompetent marketers. And they do things complicatedly to mask their own insecurities and incompetencies.Marketers admire complexity but resist simplicity. They distrust it. They fear it.
Keywords: Marketing